(untitled) (Proceedings of the Global Public Health Conference, 2019)
The tobacco epidemic, one of the biggest public health threats, is the leading modifiable cause of non-communicable diseases in the Philippines. To protect the public from the ill effects of smoking, the local health board developed a “CLEAN Strategy” after the legislative committee signed the “Comprehensive Smoke-Free Ordinance in the Municipality of Limasawa” in 2016 which prohibits smoking and selling cigarettes in all public places and within 100 meters from these places. The main goal of this study was to complete a descriptive evaluation of the program implementation using the Theory-driven Evaluation grounded on HT Chen’s Conceptual Framework of Program Theory. This study aims specifically at documenting the association of the CLEAN Strategy to the trend in the smoking prevalence, enrollment to the smoking cessation clinic, tobacco-related mortality and morbidity. A total of 381 smokers took part in this descriptive study and data were collected biannually using the Fagerstrom Test for Nicotine Dependence. Data were also collected from the Annual Mortality and Morbidity Report of the Municipality of Limasawa from 2016-2018. Analysis of trends revealed that the intervention resulted to a 16% decrease in the prevalence of smokers from 2016 to 2017 and 30% decrease in 2018. Enrollment to the Smoking Cessation Clinic increased, with good follow up from the enrollees. Tobacco-related mortality and morbidity also significantly decreased from 2016-2018. It appears that the “CLEAN Strategy” of the municipality has lead to improved health outcomes through reduction of smoking prevalence, decrease in tobacco-related morbidity and mortality and increased enrollment in the smoking cessation clinic. The study suggests a community-based intervention that can be implemented to low-resource rural areas to achieve good health outcomes through the prevention of diseases caused by smoking.